The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fphys.2019.00793
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dynamics, Record of Ticks Infesting Humans, Wild and Domestic Animals and Molecular Phylogeny of Rhipicephalus microplus in Khyber Pakhtunkhwa Pakistan

Abstract: Although ticks prevalent in various agro-systems of Pakistan are associated with economic losses, information is still missing about the tick’s diversity, hosts they infest, seasonal dynamics and molecular phylogeny of Rhipicephalus microplus in Khyber Pakhtunkhwa (KP) Pakistan. This study for the first time enlisted ticks infesting diverse hosts including humans in various regions of KP. A total of 8,641 ticks were collected across the northern, southern and central regions of KP and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 67 publications
10
91
0
Order By: Relevance
“…This study provides the first insight into the molecular diversity of ticks, TBPs and endosymbionts in ticks from small ruminants in the FATA, Pakistan. The occurrence of Hyalomma and Rhipicephalus species characterized in our study is consistent with what has been reported previously from small and large ruminants in selected areas of Pakistan [8,15,50]. However, this study provides the first genetic evidence for Hs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study provides the first insight into the molecular diversity of ticks, TBPs and endosymbionts in ticks from small ruminants in the FATA, Pakistan. The occurrence of Hyalomma and Rhipicephalus species characterized in our study is consistent with what has been reported previously from small and large ruminants in selected areas of Pakistan [8,15,50]. However, this study provides the first genetic evidence for Hs.…”
Section: Discussionsupporting
confidence: 92%
“…Although a number of studies have assessed the prevalence of ticks and tick-borne diseases (TTBDs) of small ruminants in different areas of Pakistan [8][9][10][11][12][13][14][15][16][17][18][19], there is a paucity of information from the FATA. Moreover, no study has yet investigated the presence, prevalence and diversity of tick-borne pathogens (TBPs) of small ruminants in this region.…”
Section: Introductionmentioning
confidence: 99%
“…and Rhipicephalus spp. [1015]. These ticks are responsible for transmitting three important TBDs in cattle and buffaloes, including anaplasmosis (caused by Anaplasma centrale and A. marginale ), babesiosis (caused by Babesia bigemina and B. bovis ) and tropical theileriosis (caused by Theileria annulata ) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the non-parasitic tick stages do not move too much, and the main territorial spread of ticks is by hosts (Ogden et al, 2013). Hence, the distance to which a tick is transported from its environmental origin where it has naturally detached (and eventually collected), highly depends on the movement and migration pattern of the hosts (de la Fuente et al, 2015;Abid et al, 2019). For long distance migrators, such as birds, dispersal can be significant, and the origin of ticks can be very distant.…”
Section: Introductionmentioning
confidence: 99%